Literatur Review: Aspek Perpajakan Dan Strategi Transfer Pricing Bagi Perusahaan Multinasional - Muhammad Rizqi Ausa’ie; Hasim As’ari (Jurnal Akuntan Publik, 2025)
Transfer Pricing is one of the many terms for policies regulated by national and multinational companies in determining the transfer price of a transaction, be it the price of services, goods, or intangible assets. The main purpose of transfer pricing is to evaluate and measure company performance, but in practice transfer pricing is often used by multinational companies to minimize the amount of tax paid through price engineering that is transferred between divisions or between companies that have special relationships. A special relationship is an ownership relationship between one company and another company and this relationship occurs because of a relationship between one party and another that is not contained in an ordinary relationship. Based on the company's point of view, transfer pricing is very useful for reducing costs and corporate income tax. However, from the government's point of view, transfer pricing engineering carried out in transfer pricing practices can reduce potential government revenue, especially from the tax sector because multinational companies tend to shift their tax obligations from countries with high taxes to countries with low taxes. Thus, to regulate the transfer price, the law gives authority to the tax authorities to re-determine the amount of the transfer price between parties who have a special relationship.